Modified asphalt for heavy-duty pavement and preparation method thereof

By introducing the interlocking cross-linking structure of modified ethylene-vinyl acetate copolymer and high-performance raw materials such as mullite powder in asphalt, the problem of poor thermal stability of asphalt at extreme temperatures is solved, and the thermal stability of asphalt is significantly improved and Compressive strength extends the service life of the road and improves driving safety.

CN119286269AActive Publication Date: 2025-01-10SHANBEI GUOLIN HIGHWAY MAINTENANCE ENG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411638294.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-01-10
Estimated Expiration
2044-11-16

AI Technical Summary

Technical Problem

Asphalt has poor thermal stability under extreme temperature conditions, resulting in damage such as cracks and ruts on the road, affecting the driving safety and service life of the road.

Method used

Modified ethylene-vinyl acetate copolymer forms an interlocking cross-linking structure with asphalt, combining high-performance raw materials such as mullite powder and polyphosphoric acid to enhance the thermal stability and compressive strength of asphalt, and through alkyl glycosides and itaconic anhydride Improve material uniformity and chemical bonding to form a tight spatial network structure.

Benefits of technology

It significantly improves the thermal stability and compressive strength of asphalt, can maintain stability under high temperature and heavy load conditions, extend the service life of the road surface and improve driving safety.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of road building materials, and particularly discloses modified asphalt for a heavy-duty pavement and a preparation method of the modified asphalt. The modified asphalt is prepared from the following raw materials in parts by weight: 0.5 to 1.2 parts of polyphosphoric acid, 8 to 10 parts of modified ethylene-vinyl acetate copolymer, 70 to 80 parts of matrix asphalt, 3 to 5 parts of curing agent, 1 to 3 parts of alkyl glycoside, 9 to 12 parts of mullite powder and 2 to 3 parts of itaconic anhydride, the preparation method comprises the following steps: heating the matrix asphalt to 160-170 DEG C, then adding the modified ethylene-vinyl acetate copolymer, itaconic anhydride and polyphosphoric acid, continuously stirring and reacting for 1-2 hours, then adding the mullite powder, alkyl glycoside and the curing agent, then shearing and stirring at a high speed for 30-60 minutes, and setting the stirring speed to be 3500-4000 r / min, thereby obtaining the modified asphalt. The composition disclosed by the invention can be used for paving heavy-duty pavements, and has the advantages of good thermal stability and high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road construction materials, and more specifically, to a modified asphalt for heavy-load pavement and a preparation method thereof. Background Art

[0002] Asphalt, an indispensable key material in road construction, has physical and mechanical properties that directly determine the lifespan and driving safety of the pavement. This is especially true in heavy traffic environments, where pavements must withstand the immense impact of heavy vehicles and constant friction and wear. As a viscoelastic-plastic material, while possessing a certain degree of flexibility and adhesion, its performance is highly susceptible to the dual effects of ambient temperature and load.

[0003] During the scorching summer heat, asphalt softens significantly as ambient temperatures continue to rise. This change can severely weaken the overall stability of the asphalt mixture. When the road surface is repeatedly traversed by heavy vehicles, the softened asphalt is unable to effectively resist wheel indentations, leading to rutting and slippage, which seriously impacts road smoothness and driving safety.

[0004] During sudden drops in temperature or prolonged low temperatures in winter, asphalt becomes hard and brittle, significantly reducing its ability to adapt to deformation. Under the combined influence of heavy vehicle loads and thermal stresses, the pavement is more susceptible to functional damage, such as cracking. These cracks not only further weaken the pavement's structural strength but also accelerate the intrusion of moisture and other harmful substances, accelerating the aging process and shortening its service life.

[0005] In summary, the thermal stability of asphalt remains a pressing technical challenge in road construction. Asphalt with poor thermal stability is prone to performance changes under extreme temperatures, leading to pavement cracking, rutting, and other damage, seriously impacting road safety and service life. Therefore, the development of modified asphalt that can effectively improve its thermal stability is crucial. Summary of the Invention

[0006] In order to improve the thermal stability of asphalt, the present application provides a modified asphalt for heavy-load pavement and a preparation method thereof.

[0007] In the first aspect, the present application provides a modified asphalt for heavy-load pavement, which adopts the following technical solution: A modified asphalt for heavy-load pavement, comprising the following raw materials in parts by weight: 0.5-1.2 parts of polyphosphoric acid, 8-10 parts of modified ethylene-vinyl acetate copolymer, 70-80 parts of base asphalt, 3-5 parts of curing agent, 1-3 parts of alkyl glycoside, 9-12 parts of mullite powder, and 2-3 parts of itaconic anhydride.

[0008] By adopting this technical solution, the modified ethylene-vinyl acetate copolymer (EVA) exhibits excellent compatibility with asphalt and can be evenly dispersed in the asphalt. The EVA copolymer possesses excellent elasticity and toughness, reacting with basic groups on the asphalt surface to form strong chemical bonds, enhancing the overall stability of the material. Lightweight components in the asphalt are absorbed between the molecular chains of the modified ethylene-vinyl acetate copolymer (EVA), causing the modified EVA copolymer to swell. The two then undergo a cross-linking reaction, forming an interlocking structure between the EVA and the asphalt, thereby improving the thermal stability and compressive strength of the asphalt.

[0009] Mullite powder is a high-performance inorganic filler. Its tiny particle size and unique crystal structure enable it to tightly fill the voids in asphalt, forming a denser structure. This significantly improves the compressive strength and modulus of asphalt. It also works synergistically with EVA to enhance the thermal stability and mechanical properties of asphalt.

[0010] Polyphosphoric acid can enhance the grafting effect between EVA and asphalt, thereby helping the modified asphalt and EVA to form a tighter and more stable spatial network structure. This allows the modified asphalt to effectively resist deformation caused by external loads and temperature changes, and improves the thermal stability and compressive strength of the modified asphalt. Alkyl glycoside, as a surfactant, can improve the wettability between asphalt and aggregate, enhancing the uniformity and stability of the asphalt mixture. Itaconic anhydride, as an organic acid anhydride, can react with certain functional groups in asphalt to form more stable chemical bonds. This chemical bonding not only improves the weathering and aging resistance of asphalt, but also improves the rheological properties of asphalt to a certain extent, further increasing the compressive strength of asphalt.

[0011] Optionally, the modified ethylene-vinyl acetate copolymer comprises the following raw materials in parts by weight: 0.1-0.4 parts of catalyst, 6-8 parts of polyurethane, 2-3 parts of polydopamine, 0.5-0.8 parts of dicumyl peroxide, 10-14 parts of ethylene-vinyl acetate copolymer, and 16-20 parts of toluene.

[0012] Optionally, the modified ethylene-vinyl acetate copolymer is prepared by the following steps: Take ethylene-vinyl acetate copolymer and add it to toluene, heat the oil bath to 60-80°C and stir to dissolve, add catalyst and dicumyl peroxide, continue to heat to 80-90°C, then add polyurethane and polydopamine and stir to mix, react for 4-5 hours and then stop to obtain the modified ethylene-vinyl acetate copolymer.

[0013] The above technical solution can improve the thermal stability of asphalt by modifying ethylene-vinyl acetate copolymer. However, in practice, water infiltration can affect its thermal stability. Therefore, it is further modified with polyurethane, which has excellent waterproof properties. The EVA molecular chains undergo cross-linking and grafting reactions with the added polyurethane and polydopamine molecular chains, forming a modified EVA with a more complex structure. This not only improves the waterproof properties of ethylene-vinyl acetate copolymer but also further enhances its stability, preventing decomposition and oxidation in high temperature and high humidity environments. Furthermore, the polyurethane has good ductility, which can adapt to the natural expansion and contraction of asphalt caused by temperature changes and stress, thereby further improving the thermal stability of asphalt.

[0014] Optionally, the catalyst is an organotin catalyst.

[0015] By employing this technical solution, the organotin catalyst not only promotes chain growth during polymerization but also influences the polymer's chain structure and molecular weight distribution. By selecting the appropriate organotin catalyst, the molecular structure and properties of the modified ethylene-vinyl acetate copolymer can be manipulated, improving its flexibility and heat resistance, thereby further meeting the specific polymer performance requirements of modified asphalt for heavy-duty pavement.

[0016] Optionally, the particle size of the mullite powder is 10-20 mm.

[0017] By adopting the above technical solution, the addition of mullite powder, on the one hand, serves as a filler and utilizes its good mechanical properties as a support point in the asphalt material, thereby improving the compressive strength of the material. At the same time, mullite has high thermal stability and good thermal conductivity. By being evenly dispersed in the network structure, it can effectively conduct and disperse the heat received. The mullite powder with a particle size of 10-20 mm is selected because it has better dispersion stability and plays a better role in improving the asphalt material.

[0018] Optionally, the curing agent is sulfur.

[0019] By adopting this technical solution, sulfur, as a curing agent, can interact with asphalt molecular chains to form crystals. These crystals can significantly enhance the structural strength of asphalt and improve the bearing capacity of the road surface. At the same time, sulfur also acts as an effective cross-linking agent, forming chemical bonds between EVA molecular chains and increasing the cross-linking degree of the material, thereby further improving the mechanical properties and thermal stability of the asphalt material.

[0020] Optionally, the raw materials further include 1-3 parts of pentaerythritol stearate.

[0021] By adopting the above technical solution, pentaerythritol stearate, a high-molecular-weight liquid grease, exhibits excellent lubricity and fluidity. Adding an appropriate amount of pentaerythritol stearate to asphalt can reduce its viscosity, making it easier to construct and lay. It also improves the uniformity of the asphalt mixture, helping to evenly disperse ingredients like mullite powder and EVA throughout the asphalt, resulting in asphalt with improved thermal stability and higher compressive strength.

[0022] In a second aspect, the present application provides a method for preparing modified asphalt for heavy-load pavement, which adopts the following technical solution: A method for preparing modified asphalt for heavy-load pavement comprises the following steps: The base asphalt is heated to 160-170°C, and then modified ethylene-vinyl acetate copolymer, itaconic anhydride, and polyphosphoric acid are added to the melted asphalt. After continuing to stir and react for 1-2 hours, mullite powder, alkyl glycoside, and curing agent are added, followed by high-speed shear stirring for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the modified asphalt.

[0023] By adopting the above technical solution, modified asphalt with good thermal stability and strong compressive resistance is produced.

[0024] In summary, this application has the following beneficial effects: 1. Since this application uses ethylene-vinyl acetate copolymer, which has good compatibility with asphalt, to modify asphalt, the ethylene-vinyl acetate copolymer can be evenly dispersed in the matrix asphalt to react with the asphalt to form an interlocking cross-linked structure, making full use of its good thermal stability, thereby improving the thermal stability and compressive strength of the asphalt.

[0025] 2. This application prefers modified ethylene-vinyl acetate copolymer (EVA) that has undergone a specific modification process, with the addition of high-performance raw materials such as polyphosphoric acid and mullite powder. This modified asphalt maintains excellent stability under high-temperature and heavy-load conditions. The interlocking cross-linked structure of EVA and asphalt, the dense packing of mullite powder, and the grafting reinforcement of polyphosphoric acid collectively enhance the thermal stability and compressive strength of the asphalt, enabling the pavement to withstand greater loads and temperature fluctuations without significant deformation or damage. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents or instruments used, if the manufacturer is not specified, are commercially available conventional products.

[0028] SK-90 base asphalt has a needle penetration of 94.5 mm, a softening point of 47.3 ° C, and a density of 1.004 g / cm 3 , elongation at 15°C is greater than 150; ethylene-vinyl acetate copolymer was purchased from Dongguan Kaiwan Engineering Plastic Raw Materials Co., Ltd., brand: EV180; polyurethane was purchased from Laiyang Shengbang Silicone Technology Co., Ltd., model: SI-2045, viscosity 500-1000 MPa·s.

[0029] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps: Take 10 kg of ethylene-vinyl acetate copolymer and add it to 16 kg of toluene. Turn on the stirring device, heat the oil bath to 70 ° C and continue stirring until the EVA is dissolved, add 0.2 kg of dibutyltin dilaurate (catalyst) and 0.65 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 7 kg of polyurethane and 2.5 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.

[0030] Preparation Example 2 A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps: Take 12 kg of ethylene-vinyl acetate copolymer and add it to 18 kg of toluene. Turn on the stirring device, heat the oil bath to 60 ° C and continue stirring until the EVA is dissolved, add 0.1 kg of dibutyltin dilaurate (catalyst) and 0.5 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 8 kg of polyurethane and 3 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.

[0031] Preparation Example 3 A modified ethylene-vinyl acetate copolymer, the preparation of which comprises the following steps: Take 14 kg of ethylene-vinyl acetate copolymer and add it to 20 kg of toluene. Turn on the stirring device, heat the oil bath to 80 ° C and continue stirring until the EVA is dissolved, add 0.4 kg of dibutyltin dilaurate (catalyst) and 0.8 kg of diisopropylbenzene peroxide, continue to heat to 90 ° C, add 6 kg of polyurethane and 2 kg of polydopamine, stir and mix, stop heating after reacting for 4 hours, and naturally cool to room temperature to obtain the modified ethylene-vinyl acetate copolymer.

[0032] Preparation Example 4 A modified ethylene-vinyl acetate copolymer is different from Preparation Example 1 in that the catalyst used in this Preparation Example is an organic acid catalyst phosphoric acid.

[0033] Comparative Preparation Example 1 A modified ethylene-vinyl acetate copolymer is prepared according to the method of Preparation Example 1, except that polydopamine is not added during the modification process.

[0034] Comparative Preparation Example 2 A modified ethylene-vinyl acetate copolymer is prepared according to the method of Preparation Example 1, except that no polyurethane is added during the modification process. Example

[0035] Example 1 A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps: 75 kg of base asphalt was heated to 160°C and melted, and then 9 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2 kg of itaconic anhydride, and 1.2 kg of polyphosphoric acid were added to the melted asphalt. After continuing to stir and react for 2 hours, 11 kg of mullite powder, 3 kg of alkyl glycoside, and 3 kg of sulfur were added. Subsequently, high-speed shear stirring was performed for 30 minutes at a stirring speed of 4000 r / min to obtain the modified asphalt; the particle size of the added mullite powder was 10-20 mm.

[0036] Example 2 A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps: 70 kg of base asphalt was heated to 170°C and melted, and then 8 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 3 kg of itaconic anhydride, and 0.85 kg of polyphosphoric acid were added to the melted asphalt. After continuing to stir and react for 1.5 hours, 12 kg of mullite powder, 2 kg of alkyl glycoside, and 4 kg of sulfur were added. Subsequently, high-speed shear stirring was performed for 30 minutes at a stirring speed of 3500 r / min to obtain the modified asphalt; the particle size of the added mullite powder was 10-20 mm.

[0037] Example 3 A modified asphalt for heavy-load pavement, the preparation of which comprises the following steps: 80 kg of base asphalt was heated to 170°C and melted, and then 10 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2.5 kg of itaconic anhydride, and 0.5 kg of polyphosphoric acid were added to the melted asphalt. After continuing to stir and react for 2 hours, 9 kg of mullite powder, 1 kg of alkyl glycoside, and 5 kg of sulfur were added. Subsequently, high-speed shear stirring was performed for 30 minutes at a stirring speed of 4000 r / min to obtain the modified asphalt; the particle size of the added mullite powder was 10-20 mm.

[0038] Example 4 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 2 is used in this example.

[0039] Example 5 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 3 is used in this example.

[0040] Example 6 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Preparation Example 4 is used in this example.

[0041] Example 7 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the particle size of the mullite powder used in this example is 25-30 mm.

[0042] Example 8 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the particle size of the mullite powder used in this example is 1-10 mm.

[0043] Example 9 A modified asphalt for heavy-load pavement, which differs from Example 1 in that 1 kg of pentaerythritol stearate is further added in this example, is prepared by the following steps: 75 kg of base asphalt was heated to 160°C and melted, and then 9 kg of modified ethylene-vinyl acetate copolymer prepared in Preparation Example 1, 2 kg of itaconic anhydride, and 1.2 kg of polyphosphoric acid were added to the melted asphalt. After continuing to stir and react for 2 hours, 11 kg of mullite powder, 1 kg of pentaerythritol stearate, 3 kg of alkyl glycoside, and 3 kg of sulfur were added. Subsequently, high-speed shear stirring was performed for 30 minutes at a stirring speed of 4000 r / min to obtain the modified asphalt; the particle size of the added mullite powder was 10-20 mm.

[0044] Example 10 A modified asphalt for heavy-load pavement, which is different from Example 9 in that 3 kg of pentaerythritol stearate is added in this example.

[0045] Comparative Example Comparative Example 1 A modified asphalt for heavy-load pavement, which is different from Example 1 in that in this comparative example, an equal amount of unmodified ethylene-vinyl acetate copolymer is used to replace the modified ethylene-vinyl acetate copolymer.

[0046] Comparative Example 2 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Comparative Preparation Example 1 is used in this comparative example.

[0047] Comparative Example 3 A modified asphalt for heavy-load pavement, which is different from Example 1 in that the modified ethylene-vinyl acetate copolymer prepared in Comparative Preparation Example 2 is used in this comparative example.

[0048] Comparative Example 4 A modified asphalt for heavy-load pavement, which is different from Example 1 in that no alkyl glycoside is added in this comparative example 1.

[0049] Comparative Example 5 A modified asphalt for heavy-load pavement, which is different from Example 1 in that polyphosphoric acid is not added in this comparative example 1.

[0050] Performance testing Detection method / test method Thermal stability: A water-immersion Marshall stability test was conducted in accordance with the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTKG / E20-2011). Using an MTS universal testing machine, a four-point bending fatigue test was conducted to test the stability of the asphalt prepared using the above-mentioned mixture preparation method, with complete fracture of the asphalt material as the failure standard. The test results are shown in Table 1. Compressive strength: The test was conducted in accordance with JTJ 052-2000 "Specifications for Construction and Acceptance of Asphalt Pavements for Highway Engineering."

[0051] Table 1 Test results Marshall stability / KN Compressive strength / MPa Example 1 15.52 7.92 Example 2 15.21 7.87 Example 3 14.95 7.85 Example 4 15.11 7.75 Example 5 15.37 7.88 Example 6 14.21 7.51 Example 7 13.51 7.25 Example 8 13.28 7.17 Example 9 16.15 8.26 Example 10 16.29 8.33 Comparative Example 1 12.13 5.91 Comparative Example 2 13.56 6.87 Comparative Example 3 13.16 6.65 Comparative Example 4 14.01 6.84 Comparative Example 5 13.66 6.21 Combining Examples 1-3 with Comparative Examples 1-3 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Examples 1-3, indicating that the use of the method of the present application to modify ethylene-vinyl acetate copolymer and then adding asphalt can obtain modified asphalt with better thermal stability and higher compressive strength. Combining Example 1 with Comparative Examples 2-3, it can be seen that the use of polydopamine and polyurethane to modify ethylene-vinyl acetate copolymer can improve its waterproof performance and stability, and can promote cross-linking and grafting reactions, further improve its stability, thereby improving the thermal stability and compressive strength of the modified asphalt.

[0052] Combining Examples 1-3 and Comparative Example 4 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Example 4, indicating that alkyl glycosides can synergistically act with other substances in the raw materials to improve the wettability between asphalt and other raw materials, improve the uniformity of asphalt, and thus further improve the compressive strength of asphalt.

[0053] Combining Examples 1-3 and Comparative Example 5 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Example 5, indicating that polyphosphoric acid can enhance the network structure constructed between asphalt and EVA, enabling the modified asphalt to effectively resist deformation caused by external loads and temperature changes, and improve the thermal stability and compressive strength of the modified asphalt.

[0054] Combining Examples 1-6 and Table 1, it can be seen that the experimental data of Examples 1-5 are all better than those of Example 6, indicating that the choice of catalyst in the modification process of ethylene-vinyl acetate copolymer affects its modification effect. The selection of organic tin catalyst not only promotes the occurrence of the modification reaction but also further regulates the molecular structure and properties of the modified ethylene-vinyl acetate copolymer, improves the flexibility and heat resistance of the polymer, and thus improves the thermal stability of the modified asphalt.

[0055] Combining Example 1 with Examples 7-8 and Table 1, it can be seen that the experimental data of Example 1 are all better than those of Examples 7-8, indicating that the particle size of the added mullite powder will affect the final performance of the asphalt. Selecting mullite powder with a suitable particle size can be evenly dispersed in the asphalt material, serving as a support point, and improving the compressive strength and heat stability of the material.

[0056] Combining Example 1 with Examples 9-10 and Table 1, it can be seen that the experimental data of Examples 9-10 are all better than those of Example 1, indicating that the addition of pentaerythritol stearate can evenly distribute the various components in the asphalt, improve the uniformity of the asphalt mixture, and thus obtain asphalt with good thermal stability and high compressive strength.

[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A modified asphalt for heavy-load pavement, characterized in that: The composition comprises the following raw materials in parts by weight: 0.5-1.2 parts of polyphosphoric acid, 8-10 parts of modified ethylene-vinyl acetate copolymer, 70-80 parts of base asphalt, 3-5 parts of curing agent, 1-3 parts of alkyl glycoside, 9-12 parts of mullite powder, and 2-3 parts of itaconic anhydride.

2. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The modified ethylene-vinyl acetate copolymer comprises the following raw materials in parts by weight: 0.1-0.4 parts of catalyst, 6-8 parts of polyurethane, 2-3 parts of polydopamine, 0.5-0.8 parts of dicumyl peroxide, 10-14 parts of ethylene-vinyl acetate copolymer and 16-20 parts of toluene.

3. The modified asphalt for heavy-load pavement according to claim 2, characterized in that: The modified ethylene-vinyl acetate copolymer is prepared by the following steps: Take ethylene-vinyl acetate copolymer and add it to toluene, heat the oil bath to 60-80°C and stir to dissolve, add catalyst and dicumyl peroxide, continue to heat to 80-90°C, then add polyurethane and polydopamine and stir to mix, react for 4-5 hours and stop, to obtain the modified ethylene-vinyl acetate copolymer.

4. The modified asphalt for heavy-load pavement according to claim 2, characterized in that: The catalyst is an organotin catalyst.

5. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The particle size of the mullite powder is 10-20 mm.

6. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The curing agent is sulfur.

7. The modified asphalt for heavy-load pavement according to claim 1, characterized in that: The raw materials also include 1-3 parts of pentaerythritol stearate.

8. A method for preparing modified asphalt for heavy-load pavement according to any one of claims 1 to 7, characterized in that: The steps include: The base asphalt is heated to 160-170°C, and then modified ethylene-vinyl acetate copolymer, itaconic anhydride and polyphosphoric acid are added to the melted asphalt. After continuing to stir the reaction for 1-2 hours, mullite powder, alkyl glycoside and curing agent are added, followed by high-speed shear stirring for 30-60 minutes at a stirring speed of 3500-4000 r / min to obtain the modified asphalt.

Citation Information

Patent Citations

  • Polymer modified asphalt and preparation method thereof

    CN101531817A

  • Method for preparing plastic warm-stirred modified asphalt mixture

    CN102050599A

  • Preparation method of environment-friendly asphalt mixture additive

    CN106147252A

  • Sound-proof modified asphalt waterproof roll and preparation method thereof

    CN107641327A

  • High-viscosity modified asphalt material and preparation method thereof

    CN110041720A